αB-Crystallin Is a Target for Adaptive Immune Responses and a Trigger of Innate Responses in Preactive Multiple Sclerosis Lesions - van Noort, Johannes M.; Bsibsi, Malika; Gerritsen, Wouter H.; van der Valk, Paul; Bajramovic, Jeffrey J.; Steinman, Lawrence; Amor, Sandra (Journal of neuropathology and experimental neurology, 2010)
We present the first comparative analysis of serum immunoglobulinG reactivity profiles against the full spectrum of human myelin-associated proteins in multiple sclerosis patients and healthy control subjects. In both groups, serum antibodies display a consistent and prominent reaction to αB-crystallin (CRYAB) versus other myelin proteins. As an apparently major target for the adaptive immune system in humans, CRYAB selectively accumulates in oligodendrocytes, but not in astrocytes, or axons in so-called preactive multiple sclerosis lesions. These are clusters of activated HLA-DR-expressing microglia in myelinated normal-appearing white matter with no obvious leukocyte infiltration. They are found in most multiple sclerosis patients at all stages of disease. In these lesion areas, CRYAB in oligodendrocytes may come directly in contact with activated HLA-DR microglia. We demonstrate that CRYAB activates innate responses bymicroglia by stimulating the secretion of leukocyte-recruiting factors, including tumor necrosis factor, interleukin 17, CCL5, and CCL1, and immune-regulatory cytokines such as interleukin 10, transforming growth factor-β, and interleukin 13. Together, these data suggest that CRYAB accumulation in preactive lesions may be part of a reversible reparative local response that involves both oligodendrocytes and microglia. At the same time, however, accumulated CRYAB may represent a major target for adaptive immune responses that could contribute to progression of preactive lesions to a stage of demyelination.